Development and Psychometric Assessment of the Healthcare Provider Cultural Competence Instrument - Joshua L. Schwarz PhD; Raymond Witte PhD; Sherrill L. Sellers PhD; Rebecca A. Luzadis PhD; Judith L. Weiner PhD; Eloiza Domingo-Snyder MS; James E. Page MBA (SAGE Publishing, 2015)
This study presents the measurement properties of 5 scales used in the Healthcare Provider Cultural Competence Instrument (HPCCI). The HPCCI measures a health care provider's cultural competence along 5 primary dimensions: (1) awareness/sensitivity, (2) behaviors, (3) patient-centered communication, (4) practice orientation, and (5) self-assessment. Exploratory factor analysis demonstrated that the 5 scales were distinct, and within each scale items loaded as expected. Reliability statistics indicated a high level of internal consistency within each scale. The results indicate that the HPCCI effectively measures the cultural competence of health care providers and can provide useful professional feedback for practitioners and organizations seeking to increase a practitioner's cultural competence.